Effect of Prior Passage Through Laying Hens on Invasion of Reproductive Organs by Salmonella enteritidis - Gast, Richard K.; Guard-Bouldin, Jean; Guraya, Rupa; Holt, Peter S. (International Journal of Poultry Science, 2009)
The colonization of reproductive tissues in infected laying hens is a pivotal stage in the production of contaminated eggs that can transmit Salmonella enteritidis infections to humans. In an earlier study, a series of passages through infected laying hens increased the frequency at which an S. enteritidis isolate was deposited inside eggs. The present study evaluated the effect of in vivo passage of an S. enteritidis isolate on its ability to invade to internal tissues, including three different regions of the reproductive tract. In each of three trials, a group of laying hens was infected orally with a PT13a strain of S. enteritidis (prepared from a separate stock culture each time). After internal organ samples were removed from this first passage group for culturing at 7 days post-inoculation, an S. enteritidis isolate from the upper oviduct of an extensively infected hen was used to infect another (second passage) group of hens in each trial. The overall frequency of S. enteritidis isolation from internal organs increased between passages in only one of the three trials and no increases were observed between passages in the frequency of S. enteritidis recovery from any of the three reproductive tissue sites. Therefore, passage of S. enteritidis through infected chickens did not always select for either higher overall invasiveness or for a higher ability to colonize reproductive organs in the present study.